Intrapreneuring : - Pinchot III, Gifford (Harper & Row, 1985)
This 1985 best-selling book introduced the concept of intrapreneur, defined as a person in a large corporation empowered to create new products without being constrained by standard procedures. Large corporate structures dominate in business, and the ability to compete in a global marketplace is crucial to success. Intrapreneuring shows business leaders how large organizations can develop innovative talent from within their tanks with the speed and productivity that the coming years will demand.